2016
DOI: 10.1155/2016/5739763
|View full text |Cite
|
Sign up to set email alerts
|

Maternal High-Fat Diet during Pregnancy and Lactation Influences Obestatin and Ghrelin Concentrations in Milk and Plasma of Wistar Rat Dams and Their Offspring

Abstract: The study aims to establish the effect of a maternal high-fat diet on obestatin concentration, total ghrelin, and ghrelin/obestatin ratio during pregnancy and lactation of Wistar rats and their offspring in the first 21 days of life. On the mating day, females were randomly allocated and fed either a high-fat diet (30% of fat; HF) or breeding diet (5% fat; BD) till the 21st day of lactation. Hormones were analyzed in the blood plasma and milk of rat dams as well as in the blood plasma of their offspring. HF re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
1
12
0
6
Order By: Relevance
“…These authors suggested that their findings could have serious implications for the fertility of women born to obese mothers who would have had blunted ghrelin levels due to their obesity. Another recent study has highlighted that a maternal high fat diet during pregnancy and lactation influenced both ghrelin and obestatin levels in the dams themselves, and their offspring [20]. These findings provide further support for the need to study females throughout their ovarian cycles, as well as during pregnancy, lactation and beyond, as pre-conception events are also critical to healthy reproductive outcomes.…”
Section: Discussionmentioning
confidence: 72%
“…These authors suggested that their findings could have serious implications for the fertility of women born to obese mothers who would have had blunted ghrelin levels due to their obesity. Another recent study has highlighted that a maternal high fat diet during pregnancy and lactation influenced both ghrelin and obestatin levels in the dams themselves, and their offspring [20]. These findings provide further support for the need to study females throughout their ovarian cycles, as well as during pregnancy, lactation and beyond, as pre-conception events are also critical to healthy reproductive outcomes.…”
Section: Discussionmentioning
confidence: 72%
“…It have been also suggested that the lower food intake (although the intake was hypercaloric) despite decreased plasma leptin levels was induced by elevated levels of insulin [24] and corticosterone [25] in HF dams, as they both inhibit food and energy intake. However, Slupecka et al [8] observed no significant changes in the body weight of dams and explained that fat mobilization of triglycerides from adipose tissue and larger plasma lipid extraction in HF dams rather than increased food intake. Human population studies indicate that approximately 10 % of obese individuals have low plasma leptin levels [26].…”
Section: Discussionmentioning
confidence: 99%
“…Based upon these measurements, female rats at the appropriate point in the estrous cycle were selected for breeding. On the mating day the animals were randomly allocated to either an HF (30 % fat; 4.7 kcal/g; n = 6) or standard breeding diet (BD) (5 % fat; 3.1 kcal/g; n = 6) using a previously published protocol [8]. The porcine lard was used as the source of fat for HF diet.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations